Ghanaian Tertiary Students use of ICT (Global Journal of Human-Social Science, 2017)
The use of ICT by Ghanaian tertiary students was investigated Information on possession or access to laptop desktop smart phones and cell phone not smart and the use was obtained from 1940 students with a structured questionnaire Prevalence of ownership access was 85 1 26 3 99 5 and 46 4 for laptop desktop smart phone and cell phone not smart respectively while the use was 86 6 39 2 99 5 and 50 0 respectively Prevalence of the use of ICT for social leisure-related activities was markedly higher than for academic work Mature 31 and above years and post graduate students were more likely to use ICT for academic purpose Desktop or laptop was associated with academic work Use of laptops by students should be encouraged to limit the distraction of social applications facilitated by smart phones